White-Ceramic Conversion on Ti-29Nb-13Ta-4.6Zr Surface for Dental Applications - Akiko Obata; Eri Miura-Fujiwara; Akimitsu Shimizu; Hirotaka Maeda; Masaaki Nakai; Yoshimi Watanabe; Mitsuo Niinomi; Toshihiro Kasuga (Advances in Materials Science and Engineering)
Ti-29Nb-13Ta-4.6Zr (TNTZ) alloy has excellent mechanical properties and bone conductivity. For dental application, TNTZ surfaces were converted to white oxidized layer by a simple heat treatment in air to achieve the formation of aesthetic surfaces. The oxidized layer formed by the heat treatment at 1000°C for 0.5 or 1 hr was whiter and joined to TNTZ substrate more strongly than that formed by the treatment at 900°C. The layer consisted of TiO2 (rutile), TiNb2O7, and TiTa2O7 and possessed ~30 μm in thickness for the sample heat-treated at 1000°C and ~10 μm for that heat-treated at 900°C. The surface average roughness and the wettability increased after the heat treatment. The spreading and proliferation level of mouse osteoblast-like cell (MC3T3-E1 cell) on the heat-treated sample were almost the same as those on as-prepared one. The cell spreading on TNTZ was better than those on pure titanium (CP Ti) regardless of the heat treatment for the samples. There was no deterioration in the in vitro cell compatibility of TNTZ after the oxidized layer coating by the heat treatment.